A MXene material modified by nanosilver and its preparation method and application
Through the MXene material based on nanosilver modification, the problem of high cost and poor timeliness detection of paraquat poisoning and veterinary drug residues in the prior art is solved, and rapid and effective detection is achieved, which enhances detection stability and food safety.
Patent Information
- Application Number
- CN202410061706.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-01-16
AI Technical Summary
The prior art has problems such as high cost, poor aging and difficult detection when detecting paraquat poisoning and veterinary drug residues, and lacks a surface-enhanced Raman spectral solid substrate with good stability and low cost.
By mixing the MAX material, lithium fluoride and hydrochloric acid solution, a multi-layer MXene material was obtained, and mixed with dimethyl sulfoxide and suction filtration was used to form an MXene membrane. Then the silver nitrate solution was coated on the surface of the MXene membrane for heating, and MXene material based on nanosilver modification was prepared.
It has achieved rapid non-invasive diagnosis of paraquat poisoning patients, rapid detection of herbicides in fruits and vegetables, and efficient detection of chemical drugs added in traditional Chinese veterinary medicines, which has enhanced the stability of the surface-enhanced Raman active substrate and improved the efficiency of food safety detection.
Smart Images

Figure CN117886321B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of detection and inspection technology, and in particular to a MXene material modified with nanosilver and a preparation method and application thereof. Background Art
[0002] Paraquat is a highly polar biphenyl herbicide with strong toxicity, which is very harmful after accidental ingestion or accidental exposure. The use of liquid chromatography tandem mass spectrometry or gas chromatography tandem mass spectrometry to test patients has the disadvantages of high cost and poor timeliness. The substance has poor retention in chromatographic separation and requires a large number of operators and laboratories, making the detection of the substance very difficult.
[0003] At present, the residues of traditional Chinese veterinary drugs have gradually become an important obstacle that plagues animal husbandry and affects the development of animal husbandry. As a new type of alternative medicine, traditional Chinese veterinary drugs will not pose a threat to food safety and will gradually replace chemical drugs to a large extent. However, with the widespread use of traditional Chinese veterinary drugs, the illegal addition of chemical drug ingredients has become a new source of veterinary drug residues in animal foods. Lower detection limits, portability, and timeliness have become the inevitable requirements for the detection of traditional Chinese veterinary drug ingredients.
[0004] Surface enhanced Raman spectroscopy (SERS) is an important means of rapid and nondestructive detection of compounds. It can quickly and effectively detect toxic and harmful compounds, biological drugs, etc. in the environment. The use of surface enhanced Raman technology to carry out in vivo and in vitro biological detection has greatly expanded the application of surface enhanced Raman detection in biomedical detection. Solid substrate SERS technology refers to SERS technology designed on solid substrates such as metal substrates and non-metallic substrates. Among them, the gold substrate, silver substrate and SERS marker can play a synergistic role to improve the sensitivity of detection. However, the cost of the gold substrate is relatively high, and colloidal silver has the problem of poor stability when used in SERS technology. In summary, it is of great significance to provide a low-cost and stable SERS solid substrate. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a MXene material modified with nanosilver and a preparation method and application thereof.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a MXene material modified with nanosilver, comprising the following steps:
[0008] (1) Mixing MAX material, lithium fluoride and hydrochloric acid solution and etching to obtain a multilayer MXene material;
[0009] (2) mixing the multilayer MXene material and dimethyl sulfoxide, and filtering to obtain a MXene membrane;
[0010] (3) coating the silver nitrate solution on the surface of the MXene film and heating it to obtain the nanosilver-modified MXene material.
[0011] Preferably, the MAX material in step (1) is Ti3AlC2, Ti3AlN2, V3AlC2, V3AlN2, Nb3AlC2 or Nb3AlN2.
[0012] Preferably, the mass fraction of the hydrochloric acid solution in step (1) is 36-38%;
[0013] The mass volume ratio of the MAX material, lithium fluoride and hydrochloric acid solution in step (1) is 0.5-1.5 g: 1.1-2.1 g: 15-25 mL.
[0014] Preferably, the etching temperature in step (1) is 25 to 35° C., and the etching time is 22 to 26 hours.
[0015] Preferably, the volume ratio of the dimethyl sulfoxide in step (2) to the hydrochloric acid solution in step (1) is 25-35 mL:15-25 mL.
[0016] Preferably, the concentration of the silver nitrate solution in step (3) is 0.1-0.3 mol / L;
[0017] The mass volume ratio of the silver nitrate solution to the MXene film in step (3) is 100-120 μL: 9-11 mg.
[0018] Preferably, the heating temperature in step (3) is 35-45° C., and the heating time is 5-20 min.
[0019] The present invention also provides a MXene material modified with nano-silver prepared by the method for preparing a MXene material modified with nano-silver.
[0020] The present invention also provides the application of the MXene material modified with nanosilver in surface enhanced Raman spectroscopy technology.
[0021] The beneficial effects of the present invention are:
[0022] The present invention provides a green preparation method of a MXene material modified by nanosilver, comprising the following steps: mixing a MAX material, lithium fluoride and a hydrochloric acid solution for etching to obtain a multilayer MXene material; mixing the multilayer MXene material and dimethyl sulfoxide for suction filtration to obtain a MXene film; coating a silver nitrate solution on the surface of the MXene film for heating to obtain a MXene material modified by nanosilver. The MXene material modified by nanosilver prepared by the present invention realizes the rapid non-invasive (or low-invasive) diagnosis of paraquat poisoning patients using biological fluid samples such as blood and urine, the rapid detection of herbicides in fruits and vegetables, and the efficient detection of chemical drug additions in Chinese veterinary medicines. The MXene material modified by nanosilver can effectively realize the effect of solid-phase matrix determination of surface enhanced Raman spectroscopy, enhance the stability of the surface enhanced Raman active substrate, and is conducive to increasing the possibility of long-term storage of the material and the stability of the result determination. Patients who accidentally ingest or are accidentally exposed to paraquat will obtain qualitative and quantitative diagnosis in a short time, which is conducive to further implementation of symptomatic treatment. At the same time, it also enhances the rapid and effective detection of pesticide residues, Chinese veterinary drug residues and illegal additives in antibiotic substitute products, and improves the efficiency of food safety detection. The MXene material based on nanosilver modification prepared by the present invention can be widely used in the field of biological detection technology and has strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the preparation process of MXene materials modified with nanosilver in the present invention;
[0024] Figure 2 The UV-visible spectra, potential and particle size characterization diagrams of MXene and AgNPs in Example 1 ( Figure 2 In the figure, A is the UV-visible full-wavelength scanning spectrum of MXene and AgNPs in Example 1, B is the Zeta potential distribution diagram of MXene in Example 1, and C is the particle size distribution diagram of MXene in Example 1);
[0025] Figure 3 The scanning electron microscope characterization and EDS Mapping characterization of MXene in Example 1 ( Figure 3 In the figure, A is a scanning electron microscope characterization image of MXene in Example 1 at 500 nm, B is a scanning electron microscope characterization image of MXene in Example 1 at 1.00 μm, and C is an EDS Mapping image of MXene in Example 1);
[0026] Figure 4 Fourier infrared spectroscopy and X-ray spectrum characterization of MXene in Example 1 ( Figure 4In the figure, A is the Fourier infrared spectrum of MXene in Example 1, and B is the X-ray energy spectrum characterization diagram of MXene in Example 1);
[0027] Figure 5 The microstructure characterization diagram of MXene and MXene@AgNPs-1 in Example 1 ( Figure 5 , A is a microstructure characterization diagram of MXene at 2.0 μm in Example 1, B is a microstructure characterization diagram of MXene at 1.0 μm in Example 1, C is a microstructure characterization diagram of MXene at 200 nm in Example 1, D is a microstructure characterization diagram of MXene@AgNPs-1 at 2.0 μm in Example 1, E is a microstructure characterization diagram of MXene@AgNPs-1 at 1.0 μm in Example 1, and F is a microstructure characterization diagram of MXene@AgNPs-1 at 200 nm in Example 1);
[0028] Figure 6 This is a comparison chart of the color developer result of MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation ( Figure 6 In the figure, A is a comparison chart of the methylene blue result detected by MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation; B is a comparison chart of the rhodamine 6G result detected by MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation; C is a comparison chart of the malachite green result detected by MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation);
[0029] Figure 7 The comparison chart of the test results of the developer when the MXene@AgNPs materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are used as the substrate ( Figure 7 In the figure, A is a comparison chart of the test results of methylene blue when the MXene@AgNPs materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are used as substrates; B is a comparison chart of the test results of rhodamine 6G when the MXene@AgNPs materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are used as substrates; C is a comparison chart of the test results of malachite green when the MXene@AgNPs materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are used as substrates);
[0030] Figure 8 The detection results of MXene@AgNPs-1 obtained in Example 1 for different concentrations of color developer ( Figure 8In the figure, A is the detection result diagram of MXene@AgNPs-1 obtained in Example 1 for different concentrations of methylene blue; B is the detection result diagram of MXene@AgNPs-1 obtained in Example 1 for different concentrations of rhodamine 6G; C is the detection result diagram of MXene@AgNPs-1 obtained in Example 1 for different concentrations of malachite green);
[0031] Fig. 9 The stability test result of MXene@AgNPs-1 obtained in Example 1 on the color developer is shown in Figure ( Fig. 9 In the figure, A is a graph showing the stability test result of MXene@AgNPs-1 obtained in Example 1 for methylene blue; B is a graph showing the stability test result of MXene@AgNPs-1 obtained in Example 1 for rhodamine 6G; C is a graph showing the stability test result of MXene@AgNPs-1 obtained in Example 1 for malachite green);
[0032] Fig.10 A comparison chart of the paraquat detection result of MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation;
[0033] Fig.11 The test results of MXene@AgNPs-1 obtained in Example 1 on different concentrations of paraquat;
[0034] Fig.12 This is a comparison chart of the detection results of MXene@AgNPs-1 obtained in Example 1 on paraquat and diquat;
[0035] Fig.13 The stability test result of MXene@AgNPs-1 obtained in Example 1 on paraquat is shown;
[0036] Fig.14 This is a linear relationship diagram of the detection of paraquat by MXene@AgNPs-1 obtained in Example 1;
[0037] Fig.15 The test results of MXene@AgNPs-1 obtained in Example 1 on paraquat at different pH values;
[0038] Fig.16 The linear relationship and recovery rate of MXene@AgNPs-1 obtained in Example 1 in detecting paraquat in blood and urine ( Fig.16In the figure, A is a linear relationship diagram of the detection of paraquat in blood by MXene@AgNPs-1 obtained in Example 1, B is a linear relationship diagram of the detection of paraquat in urine by MXene@AgNPs-1 obtained in Example 1, C is a recovery result diagram of the detection of paraquat in blood by MXene@AgNPs-1 obtained in Example 1, and D is a recovery result diagram of the detection of paraquat in urine by MXene@AgNPs-1 obtained in Example 1);
[0039] Fig.17 A comparison chart of the acetaminophen results detected by MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation;
[0040] Fig.18 This is a graph showing the recovery rate of acetaminophen in Bupleurum injection detected by MXene@AgNPs-1 obtained in Example 1. DETAILED DESCRIPTION
[0041] The present invention provides a method for preparing a MXene material modified with nanosilver, comprising the following steps:
[0042] (1) Mixing MAX material, lithium fluoride and hydrochloric acid solution and etching to obtain a multilayer MXene material;
[0043] (2) mixing the multilayer MXene material and dimethyl sulfoxide, and filtering to obtain a MXene membrane;
[0044] (3) coating the silver nitrate solution on the surface of the MXene film and heating it to obtain the nanosilver-modified MXene material.
[0045] In the present invention, the MAX material in step (1) is preferably Ti3AlC2, Ti3AlN2, V3AlC2, V3AlN2, Nb3AlC2 or Nb3AlN2.
[0046] In the present invention, the mass fraction of the hydrochloric acid solution in step (1) is preferably 36-38%, more preferably 36.5-37.5%, and more preferably 37-37.2%.
[0047] In the present invention, the mass volume ratio of the MAX material, lithium fluoride and hydrochloric acid solution in step (1) is preferably 0.5-1.5 g: 1.1-2.1 g: 15-25 mL, more preferably 0.7-1.3 g: 1.3-1.8 g: 17-23 mL, and more preferably 1-1.1 g: 1.6-1.7 g: 20-21 mL.
[0048] In the present invention, the etching temperature in step (1) is preferably 25-35°C, more preferably 27-33°C, and more preferably 30-31°C; the etching time is preferably 22-26h, more preferably 23-25h, and more preferably 23.5-24h.
[0049] In the present invention, the multilayer MXene material obtained in step (1) is preferably washed with water before step (2) is performed.
[0050] In the present invention, the volume ratio of the dimethyl sulfoxide in step (2) to the hydrochloric acid solution in step (1) is preferably 25-35 mL:15-25 mL, more preferably 27-33 mL:17-23 mL, and more preferably 30-31 mL:20-21 mL. The purpose of mixing the multilayer MXene material and dimethyl sulfoxide is to use dimethyl sulfoxide to intercalate the multilayer MXene material.
[0051] In the present invention, in step (2), the mixing method is carried out by conventional technical means in the art, and the mixing is uniform, and the mixing method is preferably vortexing or oscillating; after the mixing is completed, centrifugation is performed, and the rotation speed of the centrifuge is preferably 3000-4000r / min, more preferably 3200-3800r / min, and more preferably 3500-3600r / min; the centrifugation time is preferably 10-20min, more preferably 12-18min, and more preferably 15-16min; after the centrifugation is completed, the supernatant is poured out, the remaining sample is mixed with water for redissolution, and then filtered to obtain a MXene membrane.
[0052] In the present invention, the volume ratio of the water to the dimethyl sulfoxide in step (2) is preferably 45-55 mL:25-35 mL, more preferably 47-53 mL:27-33 mL, and more preferably 50-51 mL:30-31 mL.
[0053] In the present invention, the concentration of the silver nitrate solution in step (3) is preferably 0.1 to 0.3 mol / L, more preferably 0.15 to 0.25 mol / L, and more preferably 0.2 to 0.22 mol / L.
[0054] In the present invention, the mass volume ratio of the silver nitrate solution to the MXene film in step (3) is preferably 100-120 μL: 9-11 mg, more preferably 105-115 μL: 9.5-10.5 mg, and more preferably 110-112 μL: 10-10.1 mg.
[0055] In the present invention, the coating method in step (3) is preferably dropwise addition, and the heating temperature in step (3) is preferably 35-45°C, more preferably 37-43°C, and more preferably 40-41°C; the heating time is preferably 5-20 min, more preferably 10-15 min, and more preferably 12-12.5 min. After the heating is completed, the surface of the MXene film is in a white and dry state, that is, the silver nitrate solution is reduced on the surface of the MXene film to form a silver film.
[0056] In the present invention, by adopting the specific preparation conditions given in the present invention, the MXene film and nanosilver can be effectively combined to realize the effect of solid substrate measurement of surface enhanced Raman spectroscopy. Patients who accidentally ingest or are accidentally exposed to paraquat will obtain qualitative and quantitative diagnosis in a short time, which is conducive to further implementation of symptomatic treatment.
[0057] In the present invention, MXene and AgNPs can also be prepared into a paper-based or test strip form using conventional techniques as needed.
[0058] In the present invention, the schematic diagram of the preparation process of MXene materials modified with nanosilver is as follows: Figure 1 shown.
[0059] The present invention also provides a MXene material modified with nano-silver prepared by the method for preparing a MXene material modified with nano-silver.
[0060] The present invention also provides the application of the MXene material modified with nanosilver in surface enhanced Raman spectroscopy technology.
[0061] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0062] Example 1
[0063] 1g Ti3AlC2, 1.6g lithium fluoride and 20mL of 37% hydrochloric acid solution were mixed and etched at 30°C for 24h to obtain a multilayer MXene material; the multilayer MXene material was washed with water, then vortexed with 30mL dimethyl sulfoxide, mixed evenly and centrifuged at 3500r / min for 15min. After centrifugation, the supernatant was poured out, and the remaining sample was mixed with 50mL of water for redissolution, and then filtered to obtain a MXene membrane; 100μL of 0.1mol / L silver nitrate solution was added dropwise on the surface of 10mg of the MXene membrane and heated at 40°C for 12.5min to obtain a MXene material modified with nanosilver (labeled as MXene@AgNPs-1).
[0064] The sample before filtration in this embodiment (labeled as MXene) was subjected to a UV-visible full-wavelength scanning test, a Zeta potential distribution test, and a particle size distribution test; at the same time, the nanosilver on the surface of the MXene@AgNPs-1 obtained in this embodiment was subjected to a particle size test to obtain a median particle size, and nanosilver (labeled as AgNPs) with the same median particle size was prepared and subjected to a UV-visible full-wavelength scanning test to obtain UV-visible spectra, potentials, and particle size characterization diagrams of the MXene and AgNPs in this embodiment, as shown in FIG. Figure 2 As shown; Figure 2 In the figure, A is the UV-visible full wavelength scanning spectrum of MXene and AgNPs in this embodiment, B is the Zeta potential distribution diagram of MXene in this embodiment, and C is the particle size distribution diagram of MXene in this embodiment. Figure 2 It can be seen that the MXene material prepared by the present invention has a peak in the range of 650 to 725 nm under the irradiation of ultraviolet and visible light, the average hydrodynamic particle size of the material is 1500 nm, and the average Zate potential is mainly in the range of -50 to 0 mV, and has good stability.
[0065] The sample before filtration in this embodiment (labeled as MXene) was subjected to scanning electron microscopy characterization and EDS element distribution characterization to obtain scanning electron microscopy characterization and EDS mapping characterization diagram of MXene in this embodiment, as shown in FIG. Figure 3 As shown; Figure 3 In the figure, A is a scanning electron microscope characterization image of MXene in this embodiment at 500nm, B is a scanning electron microscope characterization image of MXene in this embodiment at 1.00μm, and C is an EDS Mapping image of MXene in this embodiment. Figure 3 It can be seen that the surface of MXene material has many wrinkles and a large specific surface area, which provides sufficient sites for the modification of nanosilver particles on the MXene surface.
[0066] The sample before filtration in this embodiment (labeled as MXene) was subjected to Fourier infrared spectroscopy and X-ray spectrum characterization to obtain Fourier infrared spectroscopy and X-ray spectrum characterization diagrams of MXene in this embodiment, as shown in FIG. Figure 4 As shown; Figure 4 In the figure, A is the Fourier infrared spectrum of MXene in this embodiment, and B is the X-ray spectrum characterization of MXene in this embodiment. Figure 4 It can be seen that the groups on the surface of MXene materials are mainly -OH and -O groups, and the main elemental compositions include C, O, F, and Ti, which provide a basis for the synthesis of nanosilver materials on the surface.
[0067] The sample before filtration in this example (labeled as MXene) and the MXene@AgNPs-1 prepared in this example were subjected to microstructural characterization under a transmission electron microscope to obtain microstructural characterization diagrams of MXene and MXene@AgNPs-1 in this example, as shown in FIG. Figure 5 As shown; Figure 5 In the figure, A is the microstructure characterization diagram of MXene in this embodiment at 2.0 μm, B is the microstructure characterization diagram of MXene in this embodiment at 1.0 μm, C is the microstructure characterization diagram of MXene in this embodiment at 200 nm, D is the microstructure characterization diagram of MXene@AgNPs-1 in this embodiment at 2.0 μm, E is the microstructure characterization diagram of MXene@AgNPs-1 in this embodiment at 1.0 μm, and F is the microstructure characterization diagram of MXene@AgNPs-1 in this embodiment at 200 nm. Figure 5 It can be seen that the MXene material is a single-layer MXene material, and spindle-shaped silver nanoparticles with a particle size of 40 to 120 nm are formed on the surface of the MXene@AgNPs-1 material modified with AgNO3.
[0068] Embodiment 2-3
[0069] While keeping other conditions in Example 1 unchanged, the concentrations of the silver nitrate solution were modified to 0.2 mol / L and 0.3 mol / L, respectively, and marked as Example 2 (MXene@AgNPs-2) and Example 3 (MXene@AgNPs-3).
[0070] Comparative Examples 1-2
[0071] While keeping other conditions in Example 1 unchanged, the concentrations of the silver nitrate solution were modified to 0.02 mol / L and 0.05 mol / L, respectively, and marked as Comparative Example 1 (MXene@AgNPs-4) and Comparative Example 2 (MXene@AgNPs-5).
[0072] Take a methylene blue solution, a malachite green solution, and a rhodamine 6G solution with a concentration of 1 μg / mL, and mix them with an equal volume of a NaBr solution with a concentration of 1 mol / L to obtain a methylene blue mixed solution, a malachite green mixed solution, and a rhodamine 6G mixed solution. Taking the methylene blue mixed solution as an example, take 100 μL of the methylene blue mixed solution and drop it on the surface of MXene@AgNPs-1, and scan it using a Raman spectrometer. Set the excitation wavelength of the Raman spectrometer to 785 nm, the scanning power to 500 mW, and the integration time to 2000 ms. Scan three times, record the results, and take the average value; compare the obtained results with the theoretical Raman spectrum obtained by density functional calculation (density functional calculation of methylene blue is performed using Gaussian 16W software, and density functional theory, B3LYP 6-31G substrate was used to calculate the structure of methylene blue, and the theoretical Raman spectrum was obtained for comparison; while keeping other unchanged, the methylene blue mixed solution was replaced by the malachite green mixed solution and the rhodamine 6G mixed solution, and correspondingly, when calculating the theoretical Raman spectrum, the methylene blue was replaced by malachite green and rhodamine 6G, respectively, and the test was performed; a comparison chart of the color developer result of the MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation was obtained, as shown in FIG. Figure 6 As shown; Figure 6 In the figure, A is a comparison chart of the methylene blue result of the MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation; B is a comparison chart of the rhodamine 6G result of the MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation; C is a comparison chart of the malachite green result of the MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation. Figure 6 It can be seen that the theoretical Raman spectrum is close to the actual result. In the actual detection of methylene blue, malachite green, rhodamine 6G and other substances, the Raman shift peaks are 10 to 20 cm higher than those of the theoretical calculated spectrum. -1 This is because MXene@AgNPs-1 contains silver nanomaterials, which causes the electrons in the spectral sample to resonate with the electrons in MXene@AgNPs-1.
[0073] 100 μL of 10 μg / mL methylene blue solution was added dropwise to the surfaces of MXene@AgNPs-1, MXene@AgNPs-2, MXene@AgNPs-3, MXene@AgNPs-4, and MXene@AgNPs-5, respectively, and scanned by Raman spectrometer. The excitation wavelength of the Raman spectrometer was set to 785 nm, the scanning power was 500 mW, the integration time was 2000 ms, and the scan was performed three times. The Raman shift was recorded as 1626 cm -1 、1400cm-1 、777cm -1 The test results at the locations were averaged; other conditions were kept constant and the methylene blue solution was replaced with malachite green solution (the Raman shift was recorded as 1621 cm -1 、1399cm -1 , 1177cm-1) and Rhodamine 6G solution (recorded Raman shift of 1513cm -1 、1367cm -1 、1315cm -1 The test results at the place) were tested; a comparison chart of the test results of the developer when the MXene@AgNPs materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were used as the substrate was obtained, as shown in Figure 7 As shown; Figure 7 In the figure, A is a comparison chart of the test results of methylene blue when the MXene@AgNPs materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are used as substrates; B is a comparison chart of the test results of rhodamine 6G when the MXene@AgNPs materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are used as substrates; C is a comparison chart of the test results of malachite green when the MXene@AgNPs materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are used as substrates. Figure 7 It can be seen that when the concentration of AgNO3 solution is 0.1 mol / L, the response effect of the material tends to be stable. As the concentration of AgNO3 solution increases, the surface enhanced Raman signal of the active substrate will no longer increase significantly.
[0074] Methylene blue solution, malachite green solution, and rhodamine 6G solution of different concentrations (100 μg / mL, 50 μg / mL, 10 μg / mL, 5 μg / mL, 1 μg / mL, and 0.1 μg / mL) were mixed with an equal volume of 1 mol / L NaBr solution to obtain mixed solutions of methylene blue, malachite green, and rhodamine 6G of different concentrations. 100 μL of the mixed solution was added dropwise to the surface of MXene@AgNPs-1, and scanned using a Raman spectrometer. The excitation wavelength of the Raman spectrometer was set to 785 nm, the scanning power was 500 mW, and the integration time was 2000 ms. Each sample was scanned three times, and the results were recorded and averaged. The detection result diagram of MXene@AgNPs-1 obtained in Example 1 for different concentrations of color developers was obtained, as shown in FIG. Figure 8 As shown; Figure 8 In the figure, A is the detection result of MXene@AgNPs-1 obtained in Example 1 for different concentrations of methylene blue; B is the detection result of MXene@AgNPs-1 obtained in Example 1 for different concentrations of rhodamine 6G; C is the detection result of MXene@AgNPs-1 obtained in Example 1 for different concentrations of malachite green. Figure 8 It can be seen that under the MXene@AgNPs-1 substrate, signal molecules with a concentration of 1 μg / mL can be significantly measured, and the signal-to-noise ratio is much greater than 10, confirming that its quantification limit and detection limit are both far lower than 1 μg / mL, confirming that MXene@AgNPs-1 has high sensitivity.
[0075] 100 μL of 10 μg / mL methylene blue solution, malachite green solution, and rhodamine 6G solution were respectively added dropwise to the surface of MXene@AgNPs-1, and scanned seven times using a Raman spectrometer. The excitation wavelength of the Raman spectrometer was set to 785 nm, the scanning power was 500 mW, and the integration time was 2000 ms. The RSD value was calculated to confirm the material stability. The stability test result of MXene@AgNPs-1 obtained in Example 1 for the color developer was obtained, as shown in FIG. Fig. 9 As shown; Fig. 9 In the figure, A is the stability test result of MXene@AgNPs-1 obtained in Example 1 for methylene blue; B is the stability test result of MXene@AgNPs-1 obtained in Example 1 for rhodamine 6G; C is the stability test result of MXene@AgNPs-1 obtained in Example 1 for malachite green. Fig. 9 It can be seen that MXene@AgNPs-1 has good stability in the SERS detection of methylene blue, malachite green and rhodamine 6G. The RSDs of the 7 detection results are all less than 10%, among which the RSD of methylene blue is 5.698%, the RSD of rhodamine 6G is 8.966%, and the RSD of malachite green is 9.519%.
[0076] Gaussian 16W software was used to perform density functional calculation on paraquat, and density functional theory and B3LYP6-31G basis were used to calculate the structure of paraquat, and the theoretical Raman spectrum of paraquat was obtained; 100 μL of paraquat dibromide solution with a concentration of 100 ng / mL was added to the surface of MXene@AgNPs-1, and scanned using a Raman spectrometer to obtain its characteristic peaks. The excitation wavelength of the Raman spectrometer was set to 785 nm, the scanning power was 500 mW, and the integration time was 2000 ms. The scan was repeated three times, and the results were recorded and averaged. A comparison chart of the paraquat results detected by MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation was obtained, as shown in FIG. Fig.10 As shown. Fig.10 It can be seen that MXene@AgNPs-1 can effectively detect paraquat standard. The main characteristic peaks of paraquat are CN stretching vibration (842cm -1 ), C=C symmetric stretching vibration (1200cm -1)、CC deformation vibration (1302cm -1 ) and C=N stretching vibration (1648cm -1 ). Paraquat molecules have permanent ionic characteristics, high hydrophilicity and symmetrical structure, and tend to interact strongly with the surface through hydrogen bonds, ionic bonds and π-π bonds, which facilitate the chemical adsorption between paraquat and Ag nanoparticles.
[0077] The different concentrations (10 4 ng / mL, 10 3 ng / mL, 300ng / mL, 200ng / mL, 100ng / mL, 50ng / mL, 30ng / mL, 10ng / mL, and 1ng / mL) of paraquat dibromide solutions were mixed with an equal volume of 1mol / L NaBr solution to obtain mixed solutions of paraquat dibromide of different concentrations; 100μL of the mixed solution was added dropwise to the surface of MXene@AgNPs-1, and scanned by Raman spectrometer, setting the excitation wavelength of the Raman spectrometer to 785nm, the scanning power to 500mW, the integration time to 2000ms, and scanning each sample three times. The results were recorded and the average value was taken; the detection result diagram of MXene@AgNPs-1 obtained in Example 1 for paraquat of different concentrations was obtained, as shown in FIG. Fig.11 As shown. Fig.11 As can be seen from the figure, MXene@AgNPs-1 was used as a surface enhanced Raman spectroscopy substrate to detect paraquat solutions of different concentrations. The Raman response of paraquat solutions at different concentrations decreased with the decrease of concentration (at 842 cm -1 、1200cm -1 、1302cm -1 、1648cm -1 The intensity of the Raman peak at the
[0078] Take a paraquat dibromide solution with a concentration of 100 ng / mL and a diquat dichloride solution with a concentration of 100 ng / mL, and mix them with an equal volume of a NaBr solution with a concentration of 1 mol / L to obtain a paraquat dibromide mixed solution (marked as PQ) and a diquat dichloride mixed solution (marked as DQ). In addition, a paraquat dibromide solution with a concentration of 100 ng / mL, a diquat dichloride solution with a concentration of 100 ng / mL, and a NaBr solution with a concentration of 1 mol / L (the volume ratio of the paraquat dibromide solution, the diquat dichloride solution, and the NaBr solution is 1:1:2) are mixed to obtain a paraquat dibromide and diquat dichloride mixed solution (marked as PQ&DQ). 100 μL of the three mixed solutions were respectively added to the surface of MXene@AgNPs-1, and scanned using a Raman spectrometer. The excitation wavelength of the Raman spectrometer was set to 785 nm, the scanning power was 500 mW, the integration time was 2000 ms, and the results were recorded. A comparison chart of the detection results of paraquat and diquat of MXene@AgNPs-1 obtained in Example 1 was obtained, as shown in FIG. Fig.12 As shown. In addition to paraquat, diquat is also a common herbicide. During use, they may be mixed or used alternately. Therefore, in the event of accidental ingestion or accidental exposure, it is necessary to identify and distinguish the types of herbicides. Fig.12 It can be seen that the SERS technology based on MXene@AgNPs-1 can distinguish and identify even mixed samples without any mutual influence.
[0079] 100 μL of 100 ng / mL paraquat dibromide solution was added dropwise to the surface of MXene@AgNPs-1, and the Raman spectrometer was used for scanning 20 times in succession. The excitation wavelength of the Raman spectrometer was set to 785 nm, the scanning power was 500 mW, and the integration time was 2000 ms. The RSD value was calculated to confirm the stability of the material. The stability test result of MXene@AgNPs-1 obtained in Example 1 for paraquat was obtained, as shown in FIG. Fig.13 As shown. Fig.13 It can be obtained that the RSD is 6.05%, which proves that this method has good stability and repeatability.
[0080] Paraquat solutions of different concentrations (10 ng / mL, 30 ng / mL, 50 ng / mL, 100 ng / mL, 200 ng / mL, 300 ng / mL) were mixed with an equal volume of 1 mol / L NaBr solution to obtain paraquat mixed solutions of different concentrations; 100 μL of the mixed solution was added dropwise to the surface of MXene@AgNPs-1, and scanned by Raman spectrometer. The excitation wavelength of the Raman spectrometer was set to 785 nm, the scanning power was 500 mW, the integration time was 2000 ms, each sample was scanned three times, and the results were recorded and averaged; a linear relationship diagram of the detection of paraquat by MXene@AgNPs-1 obtained in Example 1 was obtained, as shown in FIG. Fig.14 As shown. Fig.14 It can be seen that when testing paraquat standards, although the SERS based on MXene@AgNPs-1 can be detected in the range of 1 ng / mL to 10 μg / mL, a good linear relationship can be shown in the range of 10 ng / mL to 300 ng / mL. Based on this linear range, the detection limit and quantification limit calculated by 3 times S / N and 10 times S / N are 0.29 ng / mL and 19.74 ng / mL respectively.
[0081] Take aqueous solutions with different pH values as diluents, dilute paraquat dibromide to 100 ng / mL, and drop it onto the surface of MXene@AgNPs-1. Scan it with a Raman spectrometer. Set the excitation wavelength of the Raman spectrometer to 785 nm, the scanning power to 500 mW, and the integration time to 2000 ms. Scan each sample three times, record the results, and take the average value. The test results of MXene@AgNPs-1 obtained in Example 1 for paraquat at different pH values are obtained, as shown in FIG. Fig.15 As shown. Fig.15 It can be seen that when the pH is 7, the Raman signal response is higher. Under acidic conditions, the signal is relatively stable. When the environment is alkaline, the Raman signal tends to decrease. The pH of urine and blood samples is mostly concentrated under acidic or neutral conditions. Therefore, it is confirmed that this material is effective in determining paraquat in blood and urine matrices.
[0082] 100 μL of blood / urine was extracted with 300 μL of acetonitrile and vortexed to centrifuge for precipitation. Then 300 μL of supernatant was taken and extracted with 1.5 mL of dichloromethane. The upper aqueous layer was taken and mixed with an equal volume of 1 mol / L NaBr solution to obtain a blood / urine sample. Paraquat dibromide standard was added to blood and urine samples to prepare blood and urine samples with concentrations of 50 ng / mL, 100 ng / mL, 200 ng / mL, 300 ng / mL, 400 ng / mL, and 600 ng / mL and urine samples with concentrations of 100 ng / mL, 400 ng / mL, 500 ng / mL, 700 ng / mL, 1000 ng / mL, and 1200 ng / mL, and the standard curve was prepared using the same method as above. At the same time, blood samples with paraquat concentrations of 100 ng / mL, 300 ng / mL, and 500 ng / mL and urine samples with paraquat concentrations of 300 ng / mL, 600 ng / mL, and 900 ng / mL were taken for spike recovery tests to test the recovery rate of the samples, and the linear relationship of the MXene@AgNPs-1 obtained in Example 1 in detecting paraquat in blood and urine and the recovery rate result graph were obtained, as shown in FIG. Fig.16 As shown; Fig.16 In the figure, A is the linear relationship diagram of the detection of paraquat in blood by MXene@AgNPs-1 obtained in Example 1, B is the linear relationship diagram of the detection of paraquat in urine by MXene@AgNPs-1 obtained in Example 1, C is the recovery result diagram of the detection of paraquat in blood by MXene@AgNPs-1 obtained in Example 1, and D is the recovery result diagram of the detection of paraquat in urine by MXene@AgNPs-1 obtained in Example 1. It can be obtained from 16 that when blood is used as the matrix, the linear range of MXene@AgNPs-1 as the substrate for detecting paraquat is 50-600 ng / mL, Y=2.770*X+53.72(R 2 =09926), when urine was used as the matrix, the linear range of MXene@AgNPs-1 as the substrate for paraquat detection was 100-1200 ng / mL, Y=0.8767*X-6.242(R 2 =0.9929); Paraquat standard was added to blood for spike recovery, the high, medium and low spike levels were 100 ng / mL, 300 ng / mL and 500 ng / mL, respectively, and the recovery rate was within the range of 90% to 110%; Paraquat standard was added to urine for spike recovery, the high, medium and low spike levels were 300 ng / mL, 600 ng / mL and 900 ng / mL, respectively, and the recovery rate was within the range of 90% to 110%.
[0083] Gaussian 16W software was used to perform density functional calculations on acetaminophen. Density functional theory and B3LYP 6-31G basis were used to calculate the structure of acetaminophen and obtain the theoretical Raman spectrum. Different amounts of acetaminophen were added to the Bupleurum injection to obtain Bupleurum injection with different acetaminophen concentrations (1000 ng / mL, 500 ng / mL, 300 ng / mL, 100 ng / mL, 50 ng / mL), and then extracted with methanol solution respectively. After the extraction, ten times the volume of deionized water were used to dilute them respectively, and the diluted solution was mixed with an equal volume of 1 mol / L NaBr solution. 100 μL of each was directly added dropwise to the surface of MXene@AgNPs-1, and scanned by Raman spectrometer. The excitation wavelength of the Raman spectrometer was set to 785 nm, the scanning power was 500 mW, the integration time was 2000 ms, and the scan was performed three times. The results were recorded and the average value was taken. A comparison chart of the acetaminophen result detected by MXene@AgNPs-1 obtained in Example 1 and the Raman spectrum obtained by density functional calculation was obtained, as shown in FIG. Fig.17 shown; from Fig.17 It can be seen that the theoretical Raman spectrum is different from the actual result in the range of 1200-1800 cm -1 The peak values in the range are close. In the actual detection of acetaminophen, the Raman shift peak of the theoretical calculated spectrum has occurred by 10 to 20 cm -1 The shift is due to the presence of silver nanomaterials in the MXene@AgNPs-1 substrate, which causes the electrons in the spectral sample to resonate with the electrons in MXene@AgNPs-1.
[0084] At the same time, the spiked recovery test was performed on the Bupleurum injection with different acetaminophen concentrations to test the recovery rate of the samples, and the recovery rate result graph of acetaminophen in Bupleurum injection detected by MXene@AgNPs-1 obtained in Example 1 was obtained, as shown in FIG. Fig.18 shown; from Fig.18 It can be seen that the intensity of the Raman detection signal decreases with the decrease of the acetaminophen content in Chaihu injection. When the concentration is reduced to 50ng / mL, there is still a significant peak display. It can be concluded that MXene@AgNPs materials provide important material basis data support for the detection of antibiotics and other western medicines added to Chinese veterinary medicines in the later stage.
[0085] As can be seen from the above embodiments, the present invention provides a green preparation method of MXene materials modified by nanosilver, comprising the following steps: mixing MAX materials, lithium fluoride and hydrochloric acid solution for etching to obtain a multilayer MXene material; mixing the multilayer MXene material and dimethyl sulfoxide for suction filtration to obtain a MXene film; coating the silver nitrate solution on the surface of the MXene film for heating to obtain a MXene material modified by nanosilver. The MXene material modified by nanosilver prepared by the present invention realizes the rapid non-invasive (or low-invasive) diagnosis of paraquat poisoning patients using biological fluid samples such as blood and urine, the rapid detection of herbicides in fruits and vegetables, and the efficient detection of chemical drug additions in Chinese veterinary medicines. The MXene material modified by nanosilver can effectively realize the effect of solid-phase matrix determination of surface enhanced Raman spectroscopy, enhance the stability of the surface enhanced Raman active substrate, and is conducive to increasing the possibility of long-term storage of materials and the stability of the result determination. Patients who accidentally ingest or are accidentally exposed to paraquat will obtain qualitative and quantitative diagnosis in a short time, which is conducive to further implementation of symptomatic treatment. At the same time, it also enhances the rapid and effective detection of pesticide residues, Chinese veterinary drug residues and illegal additives in antibiotic substitute products, and improves the efficiency of food safety detection. The MXene material based on nanosilver modification prepared by the present invention can be widely used in the field of biological detection technology and has strong practicality.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing MXene materials based on nanosilver modification, characterized in that: It includes the following steps: (1) Mixing MAX material, lithium fluoride and hydrochloric acid solution and etching to obtain multilayer MXene material; (2) Mixing the multilayer MXene material and dimethyl sulfoxide, filtering, and obtaining a MXene membrane; (3) coating the silver nitrate solution on the surface of the MXene film and heating it to obtain the nanosilver-modified MXene material; The mass fraction of the hydrochloric acid solution in step (1) is 36-38%; The mass volume ratio of the MAX material, lithium fluoride and hydrochloric acid solution in step (1) is 0.5-1.5 g: 1.1-2.1 g: 15-25 mL; The etching temperature in step (1) is 25-30°C and the etching time is 22-26h; The concentration of the silver nitrate solution in step (3) is 0.1-0.3 mol / L; In step (3), the mass volume ratio of the silver nitrate solution to the MXene film is 100-120 μL: 9-11 mg; The nanosilver-modified MXene material is used to determine paraquat in blood and urine matrices, herbicides in fruits and vegetables, and chemical drugs in traditional Chinese veterinary medicines.
2. The method for preparing a MXene material modified by nanosilver according to claim 1, characterized in that: The MAX material in step (1) is Ti3AlC2, Ti3AlN2, V3AlC2, V3AlN2, Nb3AlC2 or Nb3AlN2.
3. A method for preparing a MXene material based on nanosilver modification according to claim 2, characterized in that: The volume ratio of the dimethyl sulfoxide in step (2) to the hydrochloric acid solution in step (1) is 25-35 mL:15-25 mL.
4. A method for preparing a MXene material based on nanosilver modification according to claim 3, characterized in that: The heating temperature in step (3) is 35-45° C., and the heating time is 5-20 min.
5. A MXene material modified with nano-silver prepared by the method for preparing a MXene material modified with nano-silver according to any one of claims 1 to 4.
6. Application of the nanosilver-modified MXene material according to claim 5 in surface enhanced Raman spectroscopy technology.
Citation Information
Patent Citations
Preparation method and application of SERS film substrate based on MXene
CN113666373A
MXene-based quantum dot / silver nanoparticle composite material as well as preparation method and application thereof
CN115287058A